Monumentos megalíticos da freguesia de Escariz (Arouca): ponto da situação à luz dos primeiros trabalhos - Silva, Fernando Augusto Pereira da (Trabalhos de Antropologia e Etnologia, 2020)
The author presents an analysis of the Megalithic group of the parish of Escariz, council of Amuca, Portugal. ln this study, the author took an inventary of ali monuments existing in that region and tried to analyse them in the light of their space distribution and its relation to the various types of soil. The structure and objects found in the monuments excavated for the last three years were also analysed as a whole.